NNC55-0396 Reduces SH-SY5Y Cell Damage Induced by Bupivacaine Hydrochloride - Wen, Xianjie; Wu, Zhaoxia; Xu, Shiyuan (Journal of Experimental and Clinical Toxicology, 2020)
Background Local anesthetic neurotoxicity is a common complication in clinical anesthesia, which can cause permanent nerve damage in severe cases. The T-type calcium channel is an important channel for regulating the excitability of neurons. Normally, extracellular calcium ions enter the cell through the T-type calcium channel to change the excitability of neurons. When the intracellular calcium is overloaded, it can cause cell damage. Aims To investigated the roles of T-type calcium channel in the SH-SY5Y cells injury induced by the bupivacaine. Methods The SH-SY5Y cell culture model was used to observe the effect of T-type calcium channel blocker NNC55-0396 on the neurotoxicity of bupivacaine hydrochloride by MTT methold,flow cytometry, Western blotting and other methods. Results The results show that NNC55-0396 can block the T-type calcium channel of SH-SY5Y cells, improve the decrease of cell viability caused by bupivacaine hydrochloride, reduce the level of intracellular calcium ion, reduce the expression of Cleavedcaspase-3, and reduce cell apoptosis. Conclusion The above results indicate that the T-type calcium channel is involved in the SH-SY5Y cell damage caused by bupivacaine hydrochloride, and blocking the T-type calcium channel can reduce the neurotoxicity of bupivacaine hydrochloride.
Keywords: NNC55-0396; Bupivacaine; Local Anesthetic Neurotoxicity; T-Type Calcium Channel; SH-SY5Y Cells; Apoptosis